Clostridioides difficile infection: microbe-microbe interactions and live biotherapeutics - Wang, Ruojun (Frontiers in Microbiology, 2023)
Clostridioides difficile is a gram-positive, spore-forming, obligate anaerobe that infects the colon. C. difficile is estimated to cause nearly half a million cases in the US annually, and about 29,000 patients die from C. difficile infections each year. Unfortunately, the current antibiotic treatment is not ideal. While antibiotics can treat the infections, they also disrupt the gut microbiota that mediates colonization resistance against enteric pathogens, including C. difficile; disrupted gut microbiota provides a window of opportunity for recurrent infections. Therefore, therapeutics that restore the gut microbiota and suppress C. difficile are being evaluated for safety and efficacy. This review will start with mechanisms by which gut bacteria affect C. difficile pathogenesis, followed by a discussion on biotherapeutics for recurrent C. difficile infections.